Students' Perception of the Use of Arabic Language Learning Applications (Al-Kunuz and Rosetta Stone) in Online Learning in Islamic Universities - Mubarok Fatahillah; Husnul Hafidhoh (Jurnal Indonesia Sosial Teknologi, 2025)
This research aims to evaluate students' perceptions of the use of Arabic language learning applications, Al-Kunuz and Rosetta Stone, in the context of online learning in Islamic universities, especially at STAI Kuningan. The method used is a quantitative approach with a descriptive research design, involving 100 students as respondents. Data were collected through questionnaires measuring students' perceptions of the ease of use and effectiveness of the applications in improving speaking, listening, reading, and writing skills. The results showed that the Al-Kunuz app received positive ratings for improving speaking and listening skills, with average scores of 4.2 and 4.3, respectively, while the Rosetta Stone app was more effective in improving reading and writing skills, with average scores of 4.2 and 4.1. Linear regression analysis revealed a significant relationship between the use of the two apps and the improvement of students' Arabic language skills, with an R-squared value of 0.76. This indicates that 76% of the variation in Arabic language skills improvement can be explained by the use of the apps. However, several obstacles—such as unstable internet connections and the need for training in application use—hinder optimizing the use of this technology. These findings provide important insights for the development of technology-based Arabic language learning in Islamic universities, with particular attention to improving infrastructure and training for both teachers and students.